Reliability, availability, and condition monitoring of inverters of grid-connected solar photovoltaic systems - Sarita, Kumari; Saket, R.K.; Khan, Baseem (John Wiley and Sons Inc, 2023)
Reliability, Availability and Condition Monitoring (RACM) evaluation has become a critical area of interest for researchers as the output power quality of a Photo-Voltaic (PV) system depend on the reliability of its components. In this paper, the RACM of grid-connected PV systems is presented. For this, the Reliability Block Diagram (RBD) technique along with the exponential probability distribution function is used. The main objective of this work is to identify the weakest subsystem of a system in order to enhance system reliability. The condition monitoring system will be helpful in avoiding the sudden breakdown and unexpected maintenance of the system. An elaborate analysis is presented for PV system beginning from the sub-assemblies to the subsystems and then to the overall system. In addition, the subsystems are ranked based on their impact on the overall availability of the system. This is decided based on the availability importance measures. It is observed that the inverter forms the weakest subsystem in the solar system. The novelty of the proposed RACM method is that one can monitor the health status or useful life of the system regularly which is not yet explored in the literature. Most of the papers have considered that the components of PV systems are non-repairable but in this paper, the redundancy concept is explored which helps in increasing the reliability and availability of the system. When the proposed method and the results obtained are compared to existing methods, it is discovered that the proposed work outperforms them.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: reliability; solar photovoltaic systems; Distribution functions; Electric inverters; Power quality; Quality control; Solar concentrators; Solar power generation; Condition monitoring; Grid-connected; Output power; Photovoltaic systems; Probability distribution functions; Reliability block diagrams; Solar photovoltaic system